2009
DOI: 10.1126/science.1174447
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Network Regulating Lysosomal Biogenesis and Function

Abstract: Lysosomes are organelles central to degradation and recycling processes in animal cells. Whether lysosomal activity is coordinated to respond to cellular needs remains unclear. We found that most lysosomal genes exhibit coordinated transcriptional behavior and are regulated by the transcription factor EB (TFEB). Under aberrant lysosomal storage conditions, TFEB translocated from the cytoplasm to the nucleus, resulting in the activation of its target genes. TFEB overexpression in cultured cells induced lysosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

91
2,386
5
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 2,130 publications
(2,488 citation statements)
references
References 29 publications
91
2,386
5
6
Order By: Relevance
“…To determine whether the amelioration of neuropathology and restored clearance of autophagic vacuoles observed in trehalose-treated naglu –/ – mice were associated with activation of TFEB, we first investigated whether trehalose promotes TFEB nuclear translocation (a marker of TFEB activation [17]) in naglu –/ – mice. Confocal microscopy analysis of mouse brain sections stained for endogenous TFEB showed that the percentage of cells with TFEB in the nucleus increased dramatically upon oral trehalose administration (Figure 7(a–b)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether the amelioration of neuropathology and restored clearance of autophagic vacuoles observed in trehalose-treated naglu –/ – mice were associated with activation of TFEB, we first investigated whether trehalose promotes TFEB nuclear translocation (a marker of TFEB activation [17]) in naglu –/ – mice. Confocal microscopy analysis of mouse brain sections stained for endogenous TFEB showed that the percentage of cells with TFEB in the nucleus increased dramatically upon oral trehalose administration (Figure 7(a–b)).…”
Section: Resultsmentioning
confidence: 99%
“…Because such accumulation of autophagic vacuoles is considered a primary cause of neuronal degeneration [5357], the observed clearance is likely to be the key event underlying the improved disease phenotype. Furthermore, reduction of autophagic vacuoles was accompanied by increased activity of TFEB, a master regulator of lysosomal biogenesis and function [17]. Trehalose-mediated increase of autophagic flux was blocked by Atg7 knockdown, and trehalose-mediated transcriptional induction of the autophagy-lysosomal network was blocked by Tfeb knockdown, thus demonstrating that trehalose effects rely on TFEB and an active autophagy pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAMP-1 is best known for its regulation of lysosomal motility and endosomal-lysosomal fusion with autophagic vacuoles, 29 and has been shown to fluctuate with changes in lysosomal volume and/or number. 9,30 Western blot analysis indicated an increase in LAMP-1 levels following treatment with 10 μM rotenone ( Figure 6A), an effect that was significantly different vs vehicle control at 6 h but not 24 h ( Figure 6B). This increase in LAMP-1-suggests an increase in either the number or size of acidic vesicles that may be a consequence of lysosome dysfunction ( Figure 4) and inhibition of autophagic flux (Figure 2).…”
Section: Acs Chemical Neurosciencementioning
confidence: 99%
“…Conversely, LAMP-1 may also increase as a function of de novo lysosome biogenesis, as shown recently under stressful conditions and as a response to alterations in autophagy. 9,30 To address this possibility the effects of rotenone on endogenous levels of the transcription factor EB (TFEB) were assessed by Western blot analysis, as TFEB has been shown previously to regulate transcription of LAMP-1 in addition to other lysosomal targets. 9,30 Levels of TFEB at 6 and 24 h following rotenone treatment were similar in rotenone vs vehicle control cells (Figure 7), suggesting that the increase in LAMP-1 observed following rotenone treatment does not result from lysosome biogenesis, but rather from the inhibition of lysosomal degradation.…”
Section: Acs Chemical Neurosciencementioning
confidence: 99%